Peran Tindak Tutur Direktif dalam Novel Keluarga Cemara 2 Karya Arswendo Atmowiloto - Anastasya Fiandri Putri; Any Budiarti; Aries Setia Nugraha (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Directive speech acts are one of the crucial aspects in the study of linguistic pragmatics that reflect how speakers use language to influence the actions or responses of their interlocutors. Utterances such as commands, requests, orders, and suggestions are concrete examples of this speech act. A profound understanding of directive speech acts helps us comprehend the complexity of human communication and social interactions in various contexts. Directive speech acts not only dominate everyday conversations but also constitute a significant element in literature, especially in novels. This research aims to analyze the directive speech acts contained in the novel "Keluarga Cemara 2". This qualitative study primarily utilizes data from the novel "Keluarga Cemara 2" by Arswendo Atmowiloto, along with several supporting research books. The results of the analysis of directive speech acts in this novel reveal six main categories, including 27 requests, 304 questions, 25 expressions of needs, 17 prohibitions, 20 permissions, and 16 items of advice. These findings are subsequently used to develop alternative teaching materials tailored to Competency Standard 3.9, "Analyzing the Content and Language of Novels." In this context, directive speech acts constitute the linguistic analysis of the novel, focusing on those analyzed from the dialogues and monologues of the novel's characters.